(untitled) (Bangladesh Journal of Agricultural Research, 2016)
To evaluate the effect of drought stress on agro-morphological traits of lentil, an experiment was conducted using 168 F6:7 inbred lines along with their parents in RCB design with three replications. Analysis of variance revealed significant differences among lines in terms of all studied characters in both normal and stress conditions. Comparing with non-stress condition, drought stress reduced pod weight per plant, seed yield and pod number per plant to 54%, 45.3% and 42.2%, respectively. Correlation coefficient of biological yield, pod number per plant, pod weight per plant and harvest index (HI) with seed yield was positive and significant. Stepwise regression analysis showed that biological yield, HI, pod weights per plant and leaf length determined 87.6% of seed yield variations and biological yield had the most function. Maximum values of genotypic and phenotypic coefficient of variations were observed for seed yield, pod weight per plant and pod number per plant. The highest values of heritability found in leaf width (h2= 0.77), seed diameter (h2= 0.69) and plant height (h2= 0.66). Evaluation of stress tolerance index (STI) showed that lines 125 and 160 were the most tolerant lines, which could be recommended for cultivation in areas that subject to terminal drought stress. Bangladesh J. Agril. Res. 41(2): 207-219, June 2016